Pengaruh Struktur Good Corporate Governance Dan Kompensasi Bonus Terhadap Manajamen Laba - Wandani, Santika; Suyanto, Suyanto; Sari, Gustin Padwa (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
Agency theory states that if the principal (owner) and agent (manager) have different interests, a conflict is called agency conflict. This condition occurs because there is an imbalance in the control of information known as information asymmetry between management and other parties who do not have access to the company. This study aims to determine the effect of Good Corporate Governance 1; and Compensation Bonus 2; Against Earnings Management 3; in Non-Financial Companies listed on the Indonesia Stock Exchange (IDX). The type of research used in this research is quantitative. This study uses a purposive sampling technique in order to obtain 35 non-financial companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The data analysis method used is panel data regression analysis. The results of this study indicate that managerial ownership, independent commissioners and bonus compensation have no effect on earnings management. While the size of the company and the audit committee affect earnings management.